Olive oil supplementation prevents extracellular matrix deposition and reduces prooxidant markers and apoptosis in the offspring´s heart of diabetic rats - Roberti, Sabrina Lorena (2020)
Maternal diabetes induces fetal programming of cardiovascular diseases. Diabetes induced-cardiac fibrosis is a process that may start in utero and may be related to the prooxidant/proinflammatory environment. The aim of this study was to investigate the effect of a maternal diet enriched in olive oil on the levels of components and regulators of the extracellular matrix, on prooxidant markers and on apoptosis rate in the heart of 21-day-old offspring of diabetic rats. Maternal diabetes was induced by neonatal administration of streptozotocin. During pregnancy, diabetic and control rats were fed with diets supplemented or not with 6% olive oil. The heart of the offspring was studied at 21 days of age. We found increased deposition of collagen IV and fibronectin in the offspring´s heart of diabetic rats, which was prevented by the maternal diets enriched in olive oil. Increases in connective tissue growth factor were also prevented by the maternal diets enriched in olive oil. Prooxidant markers as well as apoptosis, which were increased in the heart of the offspring of diabetic rats, were prevented by the maternal olive oil dietary treatment. Our findings identified powerful effects of a maternal diet enriched in olive oil on the prevention of increased extracellular matrix deposition and increased prooxidant markers in the heart of 21-day-old offspring of diabetic rats.